Influence of Coating with Some Natural Based Materials on the Erosion Wear Behavior of Glass Fiber Reinforced Epoxy Resin - Abdul Hussein, Aseel Basim; AL-Hassani, Emad Saadi; Mohamed, Reem Alaa (Al-Khwarizmi Engineering Journal, 2015)
Abstract In the present study, composites were prepared by Hand lay-up molding. The composites constituents were epoxy resin as a matrix, 6% volume fractions of glass fibers (G.F) as reinforcement and 3%, 6% volume fractions of preparation natural material (Rice Husk Ash, Carrot Powder, and Sawdust) as filler. Studied the erosion wear behavior and coating by natural wastes (Rice Husk Ash) with epoxy resin after erosion. The results showed the non – reinforced epoxy have lower resistance erosion than natural based material composites and the specimen (Epoxy+6%glass fiber+6%RHA) has higher resistance erosion than composites reinforced with carrot powder and sawdust at 30cm , angle 60°, grin size of sand 425µm , temperature 30Ċ , 300 gm salt content in 2liter of water and 15 hour. Coating specimen with mixed epoxy resin -RHA with particles size in the range (1.4-4.2) µm improves erosion wear resistance characteristics of the coated specimen, coating thickness was (16 ± 1) μm and after erosion at (15 hour) the thickness was (10) μm . Keywords: Composites, Preparation of natural materials, Erosion wear, glass fiber, Coating.